2010
DOI: 10.1002/joc.1999
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal dynamics of precipitation extremes in southern Portugal: a geostatistical assessment study

Abstract: Most of the recent studies and projections of precipitation patterns, based on records observed in the past and climate change scenarios for the Mediterranean basin, suggest a relatively slow decrease in rainfall amounts over the years but an increase in the frequency of extreme precipitation events. These are key factors in desertification processes and these will cause social and environmental impacts in the short term, mainly because changes in heavy rainfall events may have severe implications and impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…In Calabria (southern Italy), some authors (e.g., [23]), considering an observation period of 100 years, have shown a negative trend in the heavy precipitation events, and an opposite trend in the low precipitation events. Generally, daily precipitation is studied using approaches based on indices, percentiles, thresholds, and extreme values [21,[24][25][26]. Two approaches are available when focusing on changes in extreme rainfall.…”
Section: : In August Was the Jackal Born; The Rain Fell In September;mentioning
confidence: 99%
“…In Calabria (southern Italy), some authors (e.g., [23]), considering an observation period of 100 years, have shown a negative trend in the heavy precipitation events, and an opposite trend in the low precipitation events. Generally, daily precipitation is studied using approaches based on indices, percentiles, thresholds, and extreme values [21,[24][25][26]. Two approaches are available when focusing on changes in extreme rainfall.…”
Section: : In August Was the Jackal Born; The Rain Fell In September;mentioning
confidence: 99%
“…There has been considerable interest in the study of temperature and precipitation extremes at different scales (Zolina, 2008;Durao et al, 2010;Ceasar et al, 2011) due to their great impact on agriculture, water resources, industry, environment, and society. Since temperature records show an increase in the global mean temperature between 0.4 and 0.8 • C in the last 100 yr (IPCC, 2007), studies of extreme temperature events have raised the interest of the scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of research has been carried out on daily precipitation, focusing on extreme events by means of a very heterogeneous spectrum of analysis methods, such as indices, percentiles, thresholds, and extreme value theory (Groisman et al, 2005), and it is not easy to compare different results (see discussions in Reiser and Kutie, 2010;Toreti et al, 2010;and Durao et al, 2010 among others for definitions and concepts). However, little information is available on the daily concentration of precipitation, mainly because of lack of high quality daily precipitation datasets (Brunetti et al, 2000(Brunetti et al, , 2001(Brunetti et al, , 2004Brugnara et al, 2012;Reiser and Kutiel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…across the Mediterranean basin (Norrant and Douguedroit, 2006;Moberg et al, 2006;Gallego et al, 2006;Brunet et al, 2007;Rodrigo and Trigo, 2007;Durao et al, 2010;Toreti et al, 2010). Thus, Reiser and Kutiel (2010) concluded that no generalized temporal changes have been detected in the daily rainfall regime across the Mediterranean basin, but the results depend on density of observations, study period, and area analysed; therefore, several trends in the probability of various daily rainfall categories have been suggested (Rodrigo, 2010).…”
Section: Introductionmentioning
confidence: 99%